2016
DOI: 10.1016/j.bbadis.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Frequent inactivation of MCC/CTNNBIP1 and overexpression of phospho-beta-catenin Y654 are associated with breast carcinoma: Clinical and prognostic significance

Abstract: Transcriptional activation of β-catenin is a hallmark of Wnt/β-catenin pathway activation. The MCC (Mutated in colorectal cancers) and CTNNBIP1 (catenin, beta interacting protein 1) are two candidate genes which inhibit the transcriptional activity of nuclear β-catenin. The importance of MCC and CTNNBIP1 in breast cancer (BC) development has not yet been studied in detail. For this reason, in present study, the alterations (deletion/methylation/mutation/expression) of MCC and CTNNBIP1 were analyzed in BC of In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…Also, we showed that ibuprofen promoted the expression level of CTNNBIP1 in treated GCSCs. Our finding is in agreement with the one which treats MCF7 and MDA‐MB‐231 cell lines of breast cancer by 5‐Aza‐2′‐deoxycytidine to downregulate β‐catenin and its target genes by CTNNBIP1 expression (Mukherjee et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, we showed that ibuprofen promoted the expression level of CTNNBIP1 in treated GCSCs. Our finding is in agreement with the one which treats MCF7 and MDA‐MB‐231 cell lines of breast cancer by 5‐Aza‐2′‐deoxycytidine to downregulate β‐catenin and its target genes by CTNNBIP1 expression (Mukherjee et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…CTNNBIP1 (catenin, beta interacting protein 1) blocks the β‐catenin‐TCF interaction, so negatively regulates Wnt signaling (Mukherjee et al, ; Peng et al, ). Also, we showed that ibuprofen promoted the expression level of CTNNBIP1 in treated GCSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tcf7l2 transcript was earlier reported to be highly downregulated in breast cancers relative to normal breast tissue, contributing to the activation of Wnt signaling pathway (51). Furthermore, Chd8 and Mcc, negative regulators of Wnt/β-catenin pathway (52,53), were also found deleted in these tumors (Supplementary Table 1, available at Carcinogenesis Online). The data taken together indicates that aberrant expressions of PI3K/AKT and Wnt/β-catenin signaling pathways involving the copy number-altered genes play roles in Aurora-A-driven mammary tumorigenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Salivary HSPAs may contribute to protection against oral microorganisms and maintain gingival health; extracellular HSPAs may nevertheless induce gingivitis under certain conditions, turn gingivitis into periodontitis and accelerate the loss of periodontal bone . CTNNBIP1 (catenin, beta interacting protein 1, also known as ICAT; gene ID: 56998), shown to be downregulated expressed in periodontitis, is a candidate gene that inhibits the transcriptional activity of nuclear β‐catenin . The activation of nuclear β‐catenin can inhibit the noncanonical Wnt pathway, leading to increased proliferation but reduced osteogenic differentiation of periodontal ligament stem cells .…”
Section: Discussionmentioning
confidence: 99%